DEPURATION CAPACITY OF THE TIMONHA - UBATUBA ESTUARINE SYSTEM, IN CEARÁ STATE, BRAZIL - de Morais, Jáder Onofre; Dias, Carolina Braga; Pinheiro, Lidriana de Souza (Arquivos de Ciências do Mar, 2014)
The capacity of purification of the Timonha-Ubatuba estuarine system was evaluated through the application of semi-empirical numeric models. Those models were based on hydrological and morphological characteristics of the estuary basin, culminated with the estimative of the time of discharge for the system different points. This area is located on the semiarid coast of the Brazilian northeastern region, where the rivers are intermittent and they flow only during the rainy season. The monitoring was accomplished during 2004 during both rain and dry periods, in a complete spring tide. At the dry period, practically there was no fluvial discharge, which gives rise to the dilution processes to be just controlled by the oscillation of the tide (tidal prism). On the other hand, during the rainy period the fluvial speed and discharges were capable to renew the waters of the system. During this period, the water’s residence was only in the first day. In general the Timonha-Ubatuba estuarine system presented a good capacity of renewal of its waters.